Research on cavitation erosion and wear resistance performance of coatings. (September 2015) - Qiu, Ning; Wang, Leqin; Wu, Suhuan; Likhachev, Dmitriy S.
Highlights: Wear-resistance of ceramic coating is better than that of stainless steel, cast iron and alloy steel. Erosion-resistances of coatings are inferior to that of gray cast iron, and hardly comparable to stainless steels. Excellent wear-resisting performance cannot guarantee any good erosion-resisting performance. Erosion-resistance of coating varies with thickness, thicker coating shows better performance. Under pure cavitation load, coatings make little sense. The solved "erosion" problems are effect of anti-corrosion. Abstract: Depending on the nature of the working medium and working conditions, corrosive and cavitation damage shall arise to pump's components. In industrial applications the corrosion-reducing coatings are sprayed on hydraulic components. But it is questionable whether such products actually do help under wear or cavitation loads or not. Abrasive jet wear tests were carried out to determine the wear resistance of coating materials: polymers and ceramics, cast iron, and steel of various types. The samples were loaded for five hours, and finally the wear depth was measured as a determining indicator of the sample's wear resistance. Results of investigation on anti-erosion performance of epoxy resin, ceramic and Polyurethane (PU) coatings brushed on alloy steel surface were also presented. Cavitation erosion tests were performed on the ultrasonic rig. The mass loss and surface morphology of the specimens were examined by balance analysis and 3-D laser microscopy, respectively. The investigations showed excellent wear-resisting performance of ceramic coatings, which is better than wear-resistance of stainless steel, cast iron and high chrome alloy steel. But the excellent wear-resisting performance could not guarantee a good erosion-resisting performance. The ceramic coatings' anti-erosion performances were inferior to that of gray cast iron, and hardly comparable to those of stainless steels. The basic factors that influenced coating's cavitation erosion endurance were adhesion and thickness of coatings. Analysis of coating's degradation mechanism showed that PU coatings could withstand longer incubation period thus enhancing the materials' cavitation erosion resistance. Several practical cases were analyzed, showing some guidance for coatings' application.